Kufic Calligraphy as a Digital Da‘wah Medium on @kufislami’s Instagram for Millennials: A Visual–Semiotic Case Study - Putra, Yoga Rarasto; Novitasari, Lyscha (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2025)
The development of information technology has given rise to a digital generation that is increasingly connected to various social media platforms. Instagram, as one of the most popular social media platforms, is closely tied to millennials because it provides information quickly, practically, and accessibly through mobile phones. This condition opens new opportunities for the development of Islamic da’wah to transform from conventional patterns into more creative and innovative models. The Instagram account @Kufislami represents this transformation by presenting Kufi calligraphy as a form of decorative art that serves as a medium for modern visual da’wah. This study aims to examine how Kufi calligraphy is used as a medium of digital da’wah that appeals to the millennial generation. The method employed is a case study with Charles Sanders Peirce’s visual semiotic approach, which analyzes signs, symbols, and meanings in the Kufi calligraphy works published through the @Kufislami account. This method explores how the use of visual signs in synergy with design elements such as form, composition, and color generates visually appealing and meaningful aesthetics. The research was conducted by randomly selecting samples of calligraphy posts from 2022 to 2023, featuring excerpts from verses of the Qur’an. The findings indicate that the exploration of Qur’anic verses in the form of Kufi calligraphy produces unique, aesthetic, and contextual visual da’wah messages, thereby expanding the reach of Islamic da’wah in the digital era. Khat Murabba employed in the design of Kufi calligraphy is a decorative khat that is highly flexible and can be developed into various design forms and modern trends favored by young generations.